2021
DOI: 10.3389/fcimb.2021.681937
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Dengue 4 as Dominant Serotype During 2017 Outbreak in South India and Associated Cytokine Expression Profile

Abstract: Dengue virus (DENV) infection is prevalent in tropical and subtropical regions of the world, which is fatal if untreated symptomatically. Emergence of new genotype within serotypes led to enhanced severity. The objective of the study is to identify the molecular characteristics of the DENV circulated during 2017 outbreak in Tamil Nadu, India, and to investigate the role of inflammatory cytokines in different “serotypes” and in “dengue severity”. A total of 135 suspected samples were tested for DENV infection u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 198 publications
(317 reference statements)
0
11
0
Order By: Relevance
“…Most of the subsequent spread of DENV4-I was restricted to Southeast Asian countries. Although it was introduced in India around 1945, there has been a significant increase in reported DENV4-I sequences from 2015 onwards, especially in South India (Fig 1) [28,60]. It is possible that it remained undetected due to underreporting of mild infections since the primary cases of DENV4 have been reported to cause mild disease [61,62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the subsequent spread of DENV4-I was restricted to Southeast Asian countries. Although it was introduced in India around 1945, there has been a significant increase in reported DENV4-I sequences from 2015 onwards, especially in South India (Fig 1) [28,60]. It is possible that it remained undetected due to underreporting of mild infections since the primary cases of DENV4 have been reported to cause mild disease [61,62].…”
Section: Resultsmentioning
confidence: 99%
“…DENV4 is emerging as one of the dominant serotypes in South India (Fig 1B) [28,60]. High divergence in the DENV4-Id lineage in India is largely restricted to immunodominant E and NS2A proteins, again pointing to immune evasion driving its emergence.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 studies analyzed GM-CSF, and 12 found increased levels in dengue patients, half of whom had severe dengue, in contrast with nonsevere dengue and/or healthy controls [ 12 , 37 , 38 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including 1 study in children only [ 48 ]. The increase in GM-CSF levels is evident mainly in the critical phase [ 12 , 37 , 38 , 46 , 52 ], and elevated GM-CSF levels are associated with clinical manifestations of severe dengue, such as cavitary effusion [ 46 ], hypotension [ 45 ], and encephalitis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in GM-CSF levels is evident mainly in the critical phase [ 12 , 37 , 38 , 46 , 52 ], and elevated GM-CSF levels are associated with clinical manifestations of severe dengue, such as cavitary effusion [ 46 ], hypotension [ 45 ], and encephalitis [ 48 ]. Furthermore, the expression of GM-CSF varied between the primary and secondary infections for each serotype; the upregulation of GM-CSF was found in primary DENV-1 and secondary DENV-2 infections [ 47 ]. However, three studies found no significant difference between secondary and primary infection, with or without plasma leakage, or during co-infection with malaria [ 29 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation